سیاسة الملك عبدالعزیز بین المقدرة والعفو - مداح، أمیرة بنت علی وصفی (جامعة الأزهر - كلية الدراسات الإنسانية, 2018)
سياسة الملك عبدالعزيز بين المقدرة والعفو اهتم الملك عبدالعزيز – رحمه الله – بتأصيل المبادئ الإنسانية، فقد تربى على حب الناس وعشق الخير، وامتلأت بذلك جوانحه وفاضت بها نفسه الطيبة، فكان كثير العفو رحيما نقي السريرة يحب أن يصفح عن خصومه، لم ينتصر لنفسه، وإذا جاءه خصومه معتذرين قابلهم بالبشاشة مرحبا بهم ويلاطفهم، ويمنحهم بره ومعروفة وينزلهم منازلهم من التقدير والاحترام هذا هو الملك عبدالعزيز الإنسان. هدف الدراسة: 1. توضيح فعاليات القيادة وعبقرية الشخصية عند الملك عبدالعزيز منها: الاعتدال – الاستقامة – تكامل الشخصية من حيث التوازن النفسي ومراقبة الذات مما يعكس القدرة في التعامل مع الأفراد. 2. بيان منهج وسياسة الملك عبدالعزيز في الحكم والإدارة. 3. تسليط الضوء على جانب مهم في شخصية الملك عبدالعزيز – رحمه الله – وهو العفو عند المقدرة. 4. إظهار مقدرة الملك عبدالعزيز في طريقة الحوار مع الآخر سواء خصوم أو أصدقاء. 5. استخراج الدروس والعبر المستوحاة من سياسة الملك عبدالعزيز لكسب أعداءه وتحويلهم إلى أصدقاء بل إلى سواعد تقف بجانبه وتناصره. حدود الدراسة الزمنية والمكانية: بما إن الموضوع سيتناول جانبا مهما عن شخصية الملك عبدالعزيز ومعرفة سياسته ومنهجه في إدارة الدولة ستكون الحدود الزمنية هي منذ استرداد الرياض 19 شوال 1319ه حتى وفاته في ربيع الأول 1373ه، أما الحدود المكانية فهي الحدود الجغرافية للمملكة العربية السعودية في أعقاب ملحمة التوحيد. منهج الدراسة: اتبعت الباحثة منهجية استقراء الأحداث وتتبع المصادر والمراجع حتى يتم استجلاء هذه السمة ومن ثم عرضها.
The Policy of King Abd EL-Aziz Between Potency and Amnesty King Abd EL-Aziz – may Allah mercy him – concerned with the human principles. He was brought up on the love of people and goodness. He had a very good soul. He was merciful. He liked to pardon his enemies. He was always cheerful to them. He was truely a human. The study objective:- 1- the study aims at showing the leader ship and the genious personality of King Abd EL-Aziz such as: modesty – straightness – the personality completeness through the psychological balance and self – control that reflects the potency in dealing with individuals. 2- Showing the method and policy of King Abd EL-Aziz in ruling and management. 3- Spotting on an important side of the character of King Abd EL-Aziz – may Allah mercy him – forgiveness when having potency. 4- Showing the ability of King Abd EL-Aziz in conversation with his enemies and friends. 5- Getting out the lessons and morals from the policy of King Abd EL-Aziz for winning his enemies and changing them in to friends and supporters. The study borders in time and place:- The subject deals with an Important side in King Abd EL-Aziz personality and knowing his policy and method of management the country. The time borders were since 19 Shawal 1379 H from the return of Riad till his death in Rabia Alawal 1373 H. the place borders were the geographic borders of the Saudi – Arabia Kingdom in the sequence of Tawheed Battle. The study Methodology:- The researcher has followed the method of events rereading and following the sources till reaching these characteristics them showing the results.
Keywords: الملك عبدالعزیز -- القيادة -- العدل -- العفو -- الأخلاق